Efektifitas Dakwah Virtual di Era Pandemi - Awaludin Pimay; Uswatun Niswah (Jurnal Komunikasi Islam, 2021)
Islamic proselytising (da’wah) is one of the affected-activities during the Covid-19 pandemic. The da’wah activities which are usually carried out in mosques through majlis taklim had to be stopped due to coronavirus disease, well-known as Covid-19 pandemic. This paper examines the creative da’wah efforts carried out by da’wah actors (da’i) during the pandemic period. This article argues that many da’i had undrgone Islamic preaching creatively during pandemics by utilising various digital media, through spoken (bil-lisan) and written (bil-qolam) methods, including using virtual meeting applications. The use of online applications, da’wah is able to reach wider mad’u (audience) campared to offline da’wah.